(untitled) (Agroindustrial Science, 2025)
The objective of the present study was to isolate and select wild fermentative yeast strains to be used in the production of regional alcohol beverages. Yeasts were isolated from the spontaneous fermentation of must from different fruits of Misiones province and their ability to produce ethanol, as well as their tolerance to stress factors, were evaluated. Among a total of 62 isolated yeast strains, P2, P6, P7, and P11 (isolated from pitanga), and M31 (isolated from black mulberry) were preselected for presenting greater fermentation capacity. Strains P6 and P11 proved to be the most resistant to ethanol and more osmotolerant, could grow in the presence of SO2 and presented a good ethanol yield, which was 69.6% (P6) and 77% (P11) with respect to the maximum theoretical yield. The other yeast strains showed lower tolerance to the stress factors studied. According to the results of the present study, strains P6 and P11 were selected for further research focused on the production of regional fruit wines.